Factors Affecting Job Satisfaction Among Malaysian Employees In Manufacturing Sector - Md. Hamdan, Nor Amalis (2001)
The primary objective of this study attempted to investigate the level of job satisfaction and it's association with selected variables. The study incorporates several variables such as personal characteristics, job characteristics, working environment, leadership of immediate superior, compensation, career development, participation, organizational communication and quality management, and performance appraisal process and outcomes. Most results obtained in the study were according to the researcher expectations.